2013
DOI: 10.1186/1471-2350-14-61
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1/2 mutation screening in high-risk breast/ovarian cancer families and sporadic cancer patient surveilling for hidden high-risk families

Abstract: BackgroundThe estimated ratio of hereditary breast/ovarian cancer (HBOC) based on family history is 1.5% in Latvia. This is significantly lower than the European average of 5–10%. Molecular markers like mutations and SNPs can help distinguish HBOC patients in the sporadic breast and ovarian cancer group.Methods50 patients diagnosed with HBOC in the Latvian Cancer Registry from January 2005 to December 2008 were screened for BRCA1 founder mutation-negatives and subjected to targeted resequencing of BRCA1 and BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…The BRCA1 gene mutations (5382insC, 4153delA, and C61G) were determined by multiplex polymerase chain reaction [ 31 ]. Breast cancer patients with the BRCA1 gene mutations were defined as hereditary [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The BRCA1 gene mutations (5382insC, 4153delA, and C61G) were determined by multiplex polymerase chain reaction [ 31 ]. Breast cancer patients with the BRCA1 gene mutations were defined as hereditary [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…In seven out of sixteen (44%) primary breast and ovarian cancer patients matching the criteria for BRCA1/2 testing pathogenic non-founder BRCA1/2 mutations were identified. All 7 pathogenic mutations, including 2 large deletions, are novel in populations of Latvia [ 5 , 8 ]. These results may suggest that the present practice of testing only the 3 most frequent BRCA1 pathogenic founder mutations is insufficient and fails to detect a considerable number of pathogenic mutations in BRCA1/2 .…”
Section: Discussionmentioning
confidence: 99%
“…There is little information about pathogenic BRCA1/2 non-founder mutations in Latvia. In a study published by Berzina et al, pathogenic non-founder mutations in BRCA1 and BRCA2 were identified in 4 out of 30 high-risk breast/ovarian cancer families from the Latvian population [ 8 ]. In another study published by Tihomirova et al, non-founder pathogenic mutations in BRCA1 and BRCA2 were detected in 9 out of 160 patients with breast and ovarian cancer [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer (BC) is the most commonly diagnosed malignant tumor among females in the world, and its morbidity is increasing in many countries [1]. When a patient is suspected of suffering from BC, clinicians can get diagnostic information from (i) diagnostic radiology, (ii) histopathology and cytopathology, and (iii) molecular and genetic techniques [2]. Among existing diagnostic technologies, histopathologic image of a biopsy or surgical specimen is the routine diagnostic method, and Hematoxylin-Eosin (HE) staining remains the gold criterion for BC diagnosis and grading [3].…”
Section: Introductionmentioning
confidence: 99%